Molecular cloning and expression of voltagedependent Anion Channel 2 (VDAC2) from electrically stimulated chicken for antibody development - Ahmad Hassan, Nurhidayah; Amid, Azura; Mohd Salleh, Hamzah (2012)
We earlier reported proteomic profiles indicating VDAC2 as a potential biomarker for over-stunned zchicken. The current work focused on cloning VDAC2 gene from chicken’s skeletal muscle into Escherichia coli. R A from chicken’s skeletal muscle was isolated and purified to synthesize the cDNA. After DNA amplification by proofread DNA polymerase, the PCR product was purified and inserted into pENTR-TEV-D-TOPO entry vector and transformed in One Shot Chemically Competent E. coli cells. The entry clone then were inserted into pDEST 17 cloning vector using LR recombination reaction and E.coli DH5α strain as the host. The vector construct was tranformed into E. coli BL21A1 strain for protein expression. All positive clones were identified by PCR and restriction enzyme digestion as well validated by DNA sequencing. Recombinant VDAC2 protein was purified by Ni-NTA spin-column and Western blot performed on the purified recombinant VDAC2 protein with anti-His followed by AP goat anti-rabbit revealed a 30 kDa protein band and confirmed the protein expression.